2002
DOI: 10.1038/sj.leu.2402491
|View full text |Cite
|
Sign up to set email alerts
|

Infants with acute lymphoblastic leukemia: no evidence for high methotrexate resistance

Abstract: CORRESPONDENCEInfants with acute lymphoblastic leukemia: no evidence for high methotrexate resistance Leukemia (2002) 16, 949-951. DOI: 10.1038/sj/leu/2402491 TO THE EDITORThe antifolate methotrexate (MTX) has contributed significantly to the great improvement in overall survival and central nervous system prophylaxis in patients with acute lymphoblastic leukemia (ALL) in the past 50 years. After transport into the cell, MTX is polyglutamylated with multiple glutamate residues to MTX-polyglutamates (MTXPGs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…24 However, using the in situ thymidylate synthase inhibition assay, we have no evidence for high resistance to methotrexate in infant ALL. 25 These results confirm our earlier findings in a small number of infants o1 year of age. 7 Importantly, we also confirmed in this larger series that infant ALL cells are highly sensitive to AraC, and, in addition, showed that the same was true for 2-CdA.…”
Section: Discussionsupporting
confidence: 82%
“…24 However, using the in situ thymidylate synthase inhibition assay, we have no evidence for high resistance to methotrexate in infant ALL. 25 These results confirm our earlier findings in a small number of infants o1 year of age. 7 Importantly, we also confirmed in this larger series that infant ALL cells are highly sensitive to AraC, and, in addition, showed that the same was true for 2-CdA.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast however, no protective effect of MLL -knockdown was seen for ARAC or MTX in the present study. Whilst one might expect that suppression of DNA-damage response pathways should increase resistance to both of these agents, it is interesting to note that, unlike GCs, elevated resistance to neither of these drugs is associated with MLL -rearrangement [32,33]; infants in fact are known to be generally more sensitive to ARAC [8,32]. There may therefore be some unexplained insult specificity in the role of MLL in mediating responses to DNA-damage.…”
Section: Discussionmentioning
confidence: 99%
“…For methotrexate (MTX), however, no difference in drug resistance was found 6. Variation in drug disposition with age might be another factor, since important changes in body composition and in the drug eliminating capacity of liver and kidneys take place during the first year of life.…”
Section: Introductionmentioning
confidence: 99%